Facing the Other: Novel Theories and Methods in Face Perception Research - Mark A. Williams (Frontiers Research Topics, 2016)
We rely heavily on faces during social interactions. Humans possess the ability to recognise thousands of people very quickly and accurately without effort. The serious social difficulties that follow abnormalities of the face recognition system (i.e., prosopagnosia) strongly underline the importance of typical face skills in our everyday life. Over the last fifty years, research on prosopagnosia, along with research in the healthy population, has provided insights into the cognitive and neural features behind typical face recognition. This has also been achieved thanks to non-invasive neuroimaging techniques such as functional Magnetic Resonance Imaging (fMRI), Electroencephalography (EEG), Magnetoencephalography (MEG), Diffusion Tensor Imaging (DTI) and Transcranial Magnetic Stimulation (TMS). However, there is still much debate about the cognitive and neural mechanisms of face perception. In the current Research Topic we plan to gather experimental works, opinions, commentaries, mini-reviews and reviews that focus on new or novel theories and methods in face perception research. Where is the field at the moment? Do we need to re-think the experimental procedures we have adopted so far? Again, what kind of techniques (or combination of them) and analysis methods will be important in the future? From the experimental point of view we encourage both behavioural and neuroimaging contributions (e.g., fMRI, EEG, MEG, DTI and TMS). Despite the main emphasis on face perception, memory and identification, we will also consider original works that focus on other aspects of face processing, such as expression recognition, attractiveness judgments and face imagery. In addition, animal investigations and experimental manipulations that alter face recognition abilities in typical human subjects (e.g., hypnosis) are also welcome. Overall, we are proposing a Research Topic that looks at face processing using different perspectives and welcome contributions from different domains such as psychology, neurology, neuroscience, cognitive science and philosophy. The current Research Topic evolved over the desire to acknowledge the relatively recent loss of three giants in the field: Drs. Shlomo Bentin, Truett Allison and Andy Calder. We dedicate this Research Topic to them and their pioneering studies.